Acceptance of Scientific Management by Natural Resource Dependent Communities - Priscilla Weeks; Jane M. Packard (Conservation Biology, 1997)
We explore the reaction of two resource dependent communities, west Texas ranchers and Gulf Coast oyster fishers, to scientific resource management. We examine the criteria these two social groups use to judge scientific claims, and by extension, scientific resource management. Although scientists rely on factors internal to the scientific enterprise (e.g., methodological rigor), natural resource dependent communities such as ranchers and fishers may rely on factors external to the scientific process. Such factors include the historical relationship the community has had with the managing agency, the extent to which scientific explanations match local experience, the conceptual fit between managers’ and communities’ views of the appropriate relationship between humans and nature, and the resources available to the community to argue against regulation. We conclude that (1) agencies should explore the possibility of including the experiential knowledge of natural resource users where applicable and (2) agencies should recognize that communication skills can be as important as scientific skills in reaching management goals.